Playful Learning Landscapes: Creating skill-building experiences in community spaces. Issue 4 (4th July 2019) - Schlesinger, Molly A.; Hirsh-Pasek, Kathy
Abstract : Children are always learning. Innovative initiatives that offer opportunities for learning and skill building in environments outside of school are as important as ones designed for the classroom.